Proceedings of the 18th Asia Pacific Symposium on Intelligent and Evolutionary Systems - Volume 2 - Handa, Hisashi; Ishibuchi, Hisao; Ong, Yew-Soon; Tan, Kay-Chen (Proceedings in Adaptation, Learning and Optimization,, 2015)
This book contains a collection of the papers accepted in the 18th Asia Pacific Symposium on Intelligent and Evolutionary Systems (IES 2014), which was held in Singapore from 10-12th November 2014. The papers contained in this book demonstrate notable intelligent systems with good analytical and/or empirical results.